In situ atomic force microscopy studies of growth mechanisms and surface morphology of zinc thiourea sulfate crystals. Issue 11 (3rd August 2015) - Song, Jie; Li, Mingwei; Cao, Yachao; Yin, Huawei
Abstract : In situ atomic force microscopy has been utilized in studies of the growth mechanism on the (100) face of zinc tris (thiourea) sulphate crystals growing from solution. The growth on the (100) face of pure ZTS crystal is mainly controlled by two dimensional nucleation mechanisms. The spread of nuclei, advancement of steps and formation of pits are studied. The kinetic parameters are also roughly estimated. Abstract : In situ atomic force microscopy (AFM) has been utilized in studies of the growth mechanism on the (100) face of zinc tris (thiourea) sulphate (ZTS) crystals growing from solution. The growth on the (100) face of pure ZTS crystal is mainly controlled by two dimensional (2D) nucleation mechanisms, under which the hillock is formed through layer‐by‐layer growth. It is easier to form 2D nuclei at edge dislocation and the apex of steps. The growth of 2D nucleus is in accord with nucleation‐spreading mode. The growth rate along the 〈010〉 direction is faster than that along 〈001〉 direction, both of which increase firstly and then decrease with the spread of nucleus. The kinetic coefficients of one nucleus have been roughly estimated to be 3.6 × 10 −4 cm/s and 1.8 × 10 −4 cm/s in two directions, while the activation energy E was calculated to be 53.7 kJ/mol and 55.4 kJ/mol, respectively. The 2D nuclei can be generated under lower supersaturation with the addition of EDTA. If there are several hillocks growing together, step bunches will form when the steps moving in the same direction meet each other, while the meeting of steps that move in the inverse direction will result in the separation of steps. The ability of nucleation of edge dislocation outcrops are different even they are close to each other on the same surface. When the nucleus was generated at the edge dislocation sites, it cannot spread speedily until finishes an "incubation period". Moreover, the detour of microsteps was observed due to the existence of pits. If the microcrystals attached on the surface block the step advancement, or leave the surface or are covered by the macrosteps, the pits are formed. If the macrosteps advanced across the pits, the pits will be covered and the liquid inclusions may form. However, if the microcrystal forming in the pit grow up and expose on the surface, the pit will not be covered by macrosteps. The formation of solid inclusions may be caused by the microcrystals being embedded into the single steps which move layer‐by‐layer.